2018
DOI: 10.1373/clinchem.2017.286211
|View full text |Cite
|
Sign up to set email alerts
|

Full-Size Cardiac Troponin I and Its Proteolytic Fragments in Blood of Patients with Acute Myocardial Infarction: Antibody Selection for Assay Development

Abstract: In addition to mAbs specific to the central part of cTnI (approximately aar 34-126), antibodies specific to the adjacent epitopes (approximately aar 23-36 and 126-196) could be used in assays because they recognize ≥80% of cTnI in patients' blood samples within the first 36 h after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…19 Another study showed that the N-terminal and C-terminal portions of cTnI (approximately amino acid 1-30 and 110-210) are easy to degrade. 13 Therefore, the most stable part of cTnI are amino acid residues 30 to 50 and 80 to 90. 13 Therefore, the most stable part of cTnI are amino acid residues 30 to 50 and 80 to 90.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 Another study showed that the N-terminal and C-terminal portions of cTnI (approximately amino acid 1-30 and 110-210) are easy to degrade. 13 Therefore, the most stable part of cTnI are amino acid residues 30 to 50 and 80 to 90. 13 Therefore, the most stable part of cTnI are amino acid residues 30 to 50 and 80 to 90.…”
Section: Discussionmentioning
confidence: 99%
“…15 Most of the antibodies recognize the amino acid residues 50-80 and 90-130 regions of the free cTnI can hardly recognize TnI-TnC binary and TnT-TnI-TnC ternary complex. In an immunoassay, the utilization of mAbs that are recognized to the degradative region of the analyte might lead to distinct underestimation of the biomarkers' concentration in the sample, and misdiagnosis may occur in some patients or patient groups, 13 which show that only a few epitopes located on the most stable part of cTnI could be used as an epitope for antibody development. In an immunoassay, the utilization of mAbs that are recognized to the degradative region of the analyte might lead to distinct underestimation of the biomarkers' concentration in the sample, and misdiagnosis may occur in some patients or patient groups, 13 which show that only a few epitopes located on the most stable part of cTnI could be used as an epitope for antibody development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations